A New Approach to the Thrombocytopathies. Thrombocytopathy A - Johnson, Shirley A.; Monto, Raymond W.; Caldwell, M. June (Thrombosis and Haemostasis, 1958)
A group of patients with clinical hemorrhagic disease who exhibited a prolonged bleeding time and a short prothrombin consumption time classified as Thrombocytopathy A were studied utilizing procedures involving isolated platelets and purified prothrombin. These frozen and thawed platelet extracts had poor platelet factor 3 activity which was normal after the extracts had been treated with ultrasonic oscillations. The electron microscope studies of the morphology of these platelets were abnormal. It is concluded that these platelets contain adequate amounts of platelet factor 3 but are resistant to disintegration and the activity is only liberated with difficulty.The authors wish to thank Miss Jeanne M. Riddle, M.S. medical technologist in Hematology at Henry Ford Hospital for technical assistance in providing the platelet counts for this investigation.